Church’s Response to the Ecological Crisis in a Small Country – the Case of the Roman Catholic Church in Latvia - Felcis, Weronika; Felcis, Elgars (Studia Ecologiae et Bioethicae, 2020)
Due to historical and contextual factors explained in this article, the Latvian Roman Catholic Church currently does not play any significant role in environmental protection or ecological crisis awareness building in the country. However, being called by Pope Francis in his encyclical Laudato si’, recently more of the reflection was given to the call for ecological conversion. Considering Church resources based on publicly available data, the authors describe the limitations and opportunities to strengthen the Church current response to the ecological crisis.